Blockchain based resource allocation in cloud and distributed edge computing: A survey - Baranwal, Gaurav; Kumar, Dinesh; Vidyarthi, Deo Prakash (Computer communications, 2023)
Cloud computing and distributed edge computing provide computing resources to meet the surging demands for computing caused by developments in technologies such as the Internet of Things (IoT) and Mobile communication (5G). Centralized resource allocation approaches in both computing paradigms suffer from single-point failure, tampering, modification in allocation results, and biased actions. Recently, blockchain has become popular in designing decentralized systems because of its features, including transparency, decentralization, and anti-tamper. In this paper, we provide a comprehensive survey of the research works applying blockchain in resource allocation in both computing paradigms, addressing the issues in centralized resource allocation approaches. Firstly, we identify several key research questions acting as motivation. To provide background knowledge, first, we discuss the centralized resource allocation in both computing paradigms and associated challenges. Then we discuss blockchain, its structure, working, characteristics and types, followed by its benefits to resource allocation. We identify several metrics to provide a comparative study of the works. We present a depth overview of blockchain-based resource allocation works in three domains: cloud computing, distributed edge computing and integrated edge and cloud computing. In each domain, works are summarized from three aspects: works using blockchain platforms, works providing blockchain frameworks and works advocating blockchain. We discuss consensus mechanisms in the works related to blockchain-based resource allocation, as the consensus mechanism is a fundamental part of the blockchain. Further, we provide key challenges requiring our attention. Finally, we conclude the survey. •A discussion on resource allocation in cloud and edge computing is provided.•Blockchain-based resource allocation in the cloud and edge computing is discussed.•Challenges/issues related to Blockchain-based resource allocation are identified.•Future directions related to Blockchain-based resource allocation are discussed.